THE CORRELATION BETWEEN READING HABIT AND ACADEMIC ACHIEVEMENT OF THE UNDERGRADUATE STUDENTS OF ENGLISH EDUCATION STUDY PROGRAM OF UIN RADEN FATAH PALEMBANG - Dian Erlina; Annisa Astrid; Renny Kurniasari; Heru Purwansyah (Universitas Jambi, 2019)
This research investigated the correlation between reading habit and academic achievement and explored the influnce of reading habit and academic achievement. The objectives of this research were to know if there was a significant correlation between reading habit and academic achievement and to know if there was significant influence between reading habit on academic achievement of undergraduate students of English education study program of UIN Raden Fatah Palembang. The population of this research was 482 active students and 101 students in sixth semester were taken as the sample. This research used reading habit questionnaire from Janthong (2010) to know score students’ reading habit and by collecting the students’ academic achievement. Descriptive statistic, pearson product moment correlation, and regression analysis were employed to analyze the data. Analysis using pearson product moment correlation coeffecient revealed that reading habit significantly correalted with academic achievement (r=0.565, p=000). Additonaly, the linear regression analysis showed that reading habit contributed 31.9% to academic achievement. Thus, the results indicated that there was a correlation between reading habit and academic achievement and reading habit influenced academic achievement.